Takeover Deterrent Effect of On-market Share Buyback in Australia - Dong Hai Trieu Doan; Chee Jin Yap; Gerard Gannon (Australasian Accounting, Business and Finance Journal, 2012)
This study examines whether Australian firms use on-market share buybacks to deter unwanted takeover risk. We found a statistically significant and positive relationship between a firm’s ex-ante takeover probability and its on-market share buyback activities. Our result is robust to alternative modelling techniques, namely TOBIT and Censored Quantile Regressions. This paper found evidence that in a dividend imputation credit taxation system the yield of share buyback is positively related to dividend payments. However, on-market share buyback activity is closely related to temporary cash flows rather than to permanent operating cash flows. This might indicate that, besides dividend payments, Australian firms take advantage of the financial flexibility that comes with share buybacks to redistribute nonpermanent cash flows to their shareholders.
Keywords: Share buyback; Open-market; takeover deterrent